A Finite Volume-Complete Flux Scheme for a Polluted Groundwater Site. (24th August 2016) - Eikelder, M. F. P. ten; Boonkkamp, J. H. M. ten Thije; Moonen, M. P. T.; Kumar, B. V. Rathish
Abstract : We present a model of a polluted groundwater site. The model consists of a coupled system of advection-diffusion-reaction equations for the groundwater level and the concentration of the pollutant. We use the complete flux scheme for the space discretization in combination with theϑ -method for time integration and we prove a new stability result for the scheme. Numerical results are computed for the Guarani Aquifer in South America and they show good agreement with results in literature.